Compliance of an Attorney’s Professional Profile with the Current Legislation (Law and Safety, 2020)
The article is focused on the research of actual theoretical, regulatory and practical aspects of the attorney’s professional profile. It has been noted that an important step in choosing an attorney’s profession is to study the attorney’s professional profile as a comprehensive characteristic of advocacy with the description of specific features of this profession.The main scientific approaches to defining the concept of “professional profile” have been analyzed. It has been stated that the term of “professional profile” is understood as a detailed characteristic of the profession consisting of specific requirements for the person, who intends to be engaged in it in the future, necessary for the effective professional activity of an attorney. The emphasis has been placed on the fact that there is currently no universal definition of “professional profile”.Based on the analysis of the legal literature and provisions of the current legislation, the author has comprehensively studied the structural elements of the attorney’s professional profile, enshrined in the current legislation, taking into account the existing national standards of advocacy.The author has emphasized on the lack of legal enshrinement of such qualities of an attorney as justice, depth of thinking (ability to penetrate into the essence of facts) and breadth of mind (ability to cover a wide range of issues), adherence to principles, presence of own opinion and ability to defend it, memory, critical thinking, imagination, strength of will, independence, persistence, determination, categoricalness, persuasiveness, knowledge of the client’s psyche, anticipation of his possible reactions, oratory skills, accuracy, etc.It has been concluded that the compliance with the selected structural elements (standards) of the attorney’s professional profile will create a fundamental basis for sustainable development of the legal profession of Ukraine, to introduce effective conditions for a free and competitive environment at the legal market, and to bring Ukrainian laws closer to European legislation.
Keywords: professional profile; an attorney; a lawyer; legal deontology; advocacy